PENGARUH KONSENTRASI BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Shally Hananda Putri; Septiana; Joko Sungkono (LPPM Universitas Widya Dharma, 2024)
The researcher conducted this study with the aim of finding out how study concentration and peer environment influence mathematics learning outcomes. A quantitative ex post facto approach was used in this research. The subjects were students of Grade X at State Vocational High School 1 Klaten in the academic year 2022/2023. The Cluster Random Sampling technique was employed to select samples, where Class X AKL 3 was chosen as the experimental group and Class X AKL 4 as the research group. After using questionnaires and tests to collect data, they were tested for normality, linearity, heteroscedasticity, and multicollinearity. After meeting the prerequisites, the data were analyzed using simple and multiple linear regression analysis with a significance level of . The conclusions drawn from the study are as follows: (1) There is a positive influence between study concentration and mathematics learning outcomes with a correlation coefficient of and an effective contribution of ; (2) There is a positive influence between peer environment and mathematics learning outcomes with a correlation coefficient of and an effective contribution of ; (3) There is a positive combined influence of study concentration and peer environment on mathematics learning outcomes with a coefficient of determination . Therefore, study concentration and peer environment collectively influence mathematics learning outcomes by , while other unexamined variables affect .